Two-Dimensional Planar Supercapacitor Based on Zinc Oxide/Manganese Oxide Core/Shell Nano-architecture. (1st September 2017) - Raj, C.Justin; Rajesh, Murugesan; Manikandan, Ramu; Sim, Ju Yong; Yu, Kook Hyun; Park, Sang Yeup; Song, Jun Ho; Kim, Byung Chul
Graphical abstract: Highlights: Planar supercapacitor was fabricated on FTO substrate using ZnO/MnO2 core/shell 3 D structure. α-MnO2 form of shell layer was deposited over ZnO NRs using simple SILAR technique. The shell layer was optimized by coating various SILAR cycles of MnO2 layers. Planar supercapacitor shows excellent areal capacitance and electrochemical performances Abstract: We report the fabrication and performance of zinc oxide core/manganese oxide shell (ZnO/MnO2 ) three-dimensional nanostructured planar supercapacitor. In this particular fabrication, ZnO nanorods were grown over FTO substrate followed by the successive ionic layer adsorption and reaction (SILAR) deposition of MnO2 nanostructure on ZnO nanorods. The quality of the ZnO/MnO2 electrode was optimized by performing various cycles of SILAR deposition of MnO2 layer over ZnO core. The electrode with 7 cycles of MnO2 deposition demonstrated maximum electrochemical performance with area capacitance of 14 mF cm −2 and the same condition was utilized for the fabrication of a symmetric planar supercapacitor. This ZnO/MnO2 3D architecture planar supercapacitor showed maximum area capacitance of 5 mF cm −2 in 1 M Na2 SO4 aqueous electrolyte with good energy density of 4.07 × 10 −7  Wh cm −2 and power density of 3.19 mW cm −2 . Moreover, this planar supercapacitor shows an excellent electrochemical performance with comparable long term cyclic stability.